Transcending the Self – the Illusion of Body Ownership in Immersive Virtual Reality and its Impact on Behaviour - Mel Slater (i-Perception, 2011)
Virtual reality in various forms has been around for about 40 years. It has been considered mainly as a technology that can be used to generate the illusion of a transformation of place. However, it has recently been shown that it can successfully be used to transcend the self, through illusions of body ownership and transformation. Several papers have shown that it is possible to generate in people the illusory sense of ownership of a fake body using virtual reality techniques [1-5]. This can be achieved through synchronous multisensory stimulation with respect to the real and virtual body. For example, the participant sees his or her virtual body touched, while feeling the touch synchronously and in the same place on the real body. This can also lead to illusions of body transformation, such as a thin person having the illusion of being fat [6]. Our research suggests the prime importance of a first person perspective for the illusion of ownership, however, in [7] we also found that a representation of a person in a virtual mirror with synchronous visual-motor effects also results in a body ownership illusion. Although virtual body ownership has been established, what is also of interest are the consequences of this in terms of the attitudes and behaviour of the participant who experiences the transformed body. Our very recent work suggests that the illusion of ownership of a virtual body may also result in at least short-term transformations of behaviour and attitudes of the participant towards those that are appropriate to the virtual body. This talk will describe several experiments illustrating both the illusion of body ownership and its transformative effect on attitudes and behaviour.